2023
DOI: 10.3390/vetsci10100594
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Solid-State Fermented Barley with Fibrolytic Exogenous Enzymes on Feed Utilization, and Antioxidant Status of Broiler Chickens

Doaa Ibrahim,
Hassainen I. El-sayed,
Elsabbagh R. Mahmoud
et al.

Abstract: The present and future high demand of common cereals as corn and wheat encourage the development of feed processing technology that allows for the dietary inclusion of other cereals of low nutritional value in poultry feeding. Barley grains contain anti-nutritional factors that limit their dietary inclusion in the poultry industry. The treatment of barley with solid-state fermentation and exogenous enzymes (FBEs) provides a good alternative to common cereals. In this study, barley grains were subjected to soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…The incorporation of feed (soybean and rapeseed) produced by SSF expands the availability of beneficial probiotic bacteria, such as Lactobacillus spp., which has been substantiated to induce the production of immunoglobulin in broilers [107]. Ibrahim et al [108] found that the incorporation of fermented barley in the feed was found to stimulate lysozyme activity in broiler serum [108], aligning with similar results reported by Zhu et al [109], who found an increase in serum lysozyme activity with fermented feed supplementation [109]. It is noteworthy that lysozyme, recognized as an antimicrobial enzyme, serves as a crucial factor in disrupting the cell walls of pathogenic bacteria [110].…”
Section: Why Is Ssf a Promising Strategy To Improve The Bioactivity O...mentioning
confidence: 96%
“…The incorporation of feed (soybean and rapeseed) produced by SSF expands the availability of beneficial probiotic bacteria, such as Lactobacillus spp., which has been substantiated to induce the production of immunoglobulin in broilers [107]. Ibrahim et al [108] found that the incorporation of fermented barley in the feed was found to stimulate lysozyme activity in broiler serum [108], aligning with similar results reported by Zhu et al [109], who found an increase in serum lysozyme activity with fermented feed supplementation [109]. It is noteworthy that lysozyme, recognized as an antimicrobial enzyme, serves as a crucial factor in disrupting the cell walls of pathogenic bacteria [110].…”
Section: Why Is Ssf a Promising Strategy To Improve The Bioactivity O...mentioning
confidence: 96%
“…The body weight was then calculated each week by dividing the total bird weights by the number of birds in each group. According to procedures outlined by Kishawy, et al [68] and Ibrahim, et al [69], the total body weight gain (TBWG), total feed intake (TFI), total feed conversion ratio (TFCR), and final body weight (FBW) per each replicate for the entire experimental period were estimated.…”
Section: Total Growth Performance Related Indicesmentioning
confidence: 99%
“…It has been discovered that the incorporation of amylase into poultry diets improves the utilization of dietary carbohydrates, resulting in enhanced growth performance, feed efficiency, and body weight gain (BWG) ( Ibrahim et al , 2023 ). Yuan et al (2018) reported amylase supplementation in combination with protease, or glucoamylase improves the digestibility of starch and the biodiversity of the intestinal microbes and increases the growth rate of broilers.…”
Section: Introductionmentioning
confidence: 99%